2006
DOI: 10.1007/s10529-006-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioactive Human β-defensin-3 in Escherichia coli by Soluble Fusion Expression

Abstract: A codon optimized mature human beta-defensin-3 gene (smHBD3) was synthesized and fused with TrxA to construct pET32-smHBD3 vector, which was transformed into E. coli BL21(DE3) and cultured in MBL medium. The volumetric productivity of fusion protein reached 0.99 g fusion protein l(-1), i.e. 0.21 g mature HBD3 l(-1). Ninety-six percentage of the fusion protein was in a soluble form and constituted about 45% of the total soluble protein. After cell disruption, the soluble fusion protein was separated by affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…In contrast to earlier reports about defensin production in E. coli K-12 strains (Huang et al, 2006;Pazgier and Lubkowski, 2006;Xu et al, 2006), this study reports for the first time the production of active HBD2 defensin in a probiotic E. coli strain (Nissle 1917), which is licensed as a drug for the treatment of patients suffering from e.g. diarrhea or ulcerative colitis.…”
Section: Listeria Monocytogenescontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast to earlier reports about defensin production in E. coli K-12 strains (Huang et al, 2006;Pazgier and Lubkowski, 2006;Xu et al, 2006), this study reports for the first time the production of active HBD2 defensin in a probiotic E. coli strain (Nissle 1917), which is licensed as a drug for the treatment of patients suffering from e.g. diarrhea or ulcerative colitis.…”
Section: Listeria Monocytogenescontrasting
confidence: 58%
“…It has been reported that a fusion expression system with thioredoxin (TrxA) resulted in an increased yield of soluble products (LaVallie et al 2000). This has been observed for HBD2 and HBD3 (Huang et al, 2006;Xu et al, 2006). …”
supporting
confidence: 67%
“…Escherichia coli has been used to produce small peptides composed of 21-50 amino acid residues (Huang et al 2007;Rao et al 2005). However, there has been no report on the large-scale production of a small peptide with fewer than 10 amino acid residues.…”
Section: Production Of Lactostatin (Iiaek) By Genetic Engineeringmentioning
confidence: 99%
“…Thus, soluble expression strategies are preferred to produce functional proteins efficiently, avoiding the refolding procedure. In our previous work, soluble fusion protein containing human β-defensin-2 (HBD2) and HBD3 were successfully expressed after codon optimization in E. coli as well as the cell-free system, and the purified mature HBD2 and HBD3 were fully bioactive [11][12][13][14][15][16][17]. However, the productivity (0.99 g/L) of HBD3 fusion protein in our constructed recombinant E. coli strain [12] was relatively low.…”
mentioning
confidence: 98%
“…In our previous work, soluble fusion protein containing human β-defensin-2 (HBD2) and HBD3 were successfully expressed after codon optimization in E. coli as well as the cell-free system, and the purified mature HBD2 and HBD3 were fully bioactive [11][12][13][14][15][16][17]. However, the productivity (0.99 g/L) of HBD3 fusion protein in our constructed recombinant E. coli strain [12] was relatively low. Due to the a relatively low recovery rate of mature human beta-defensin 3 after a multi-step down-stream purification process, a high-level expression of this HBD3 fusion protein is preferred for the large-scale preparation of mature recombinant HBD3.…”
mentioning
confidence: 98%